2019
DOI: 10.1111/imr.12802
|View full text |Cite
|
Sign up to set email alerts
|

Complement in malaria immunity and vaccines

Abstract: Developing efficacious vaccines for human malaria caused by Plasmodium falciparum is a major global health priority, although this has proven to be immensely challenging over the decades. One major hindrance is the incomplete understanding of specific immune responses that confer protection against disease and/or infection. While antibodies to play a crucial role in malaria immunity, the functional mechanisms of these antibodies remain unclear as most research has primarily focused on the direct inhibitory or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 168 publications
2
32
0
1
Order By: Relevance
“…These human antibody isotypes are important in mediating antibody-dependent cellular cytotoxicity and complement dependent killing, as are the mouse IgG2b and 2c isotypes elicited by AddaVax, but not alum, in the current study. Of note, Kurtovic et al 45 , 46 found that complement fixing capability of sera from immunized infant and child recipients of the RTS,S vaccine declined rapidly after immunization and this decline paralleled the decline both in IgG complement fixing isotypes and protection against severe disease. While this finding suggests further justification for the use of the AddaVax adjuvant in subsequent vaccine trials, Potocnjak et al .…”
Section: Discussionmentioning
confidence: 99%
“…These human antibody isotypes are important in mediating antibody-dependent cellular cytotoxicity and complement dependent killing, as are the mouse IgG2b and 2c isotypes elicited by AddaVax, but not alum, in the current study. Of note, Kurtovic et al 45 , 46 found that complement fixing capability of sera from immunized infant and child recipients of the RTS,S vaccine declined rapidly after immunization and this decline paralleled the decline both in IgG complement fixing isotypes and protection against severe disease. While this finding suggests further justification for the use of the AddaVax adjuvant in subsequent vaccine trials, Potocnjak et al .…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticle-induced complement activation is generally perceived as undesirable when nanoparticles administered systemically lead to complement-mediated infusion reactions (27,90). While uncontrolled complement activation can induce inflammatory and life-threatening consequences, controlled complement activation by nanoparticles may be beneficial for vaccination strategies (91)(92)(93). Opsonization of pathogens by complement proteins facilitates their uptake by antigen presenting cells via complement receptors CD21 and CD33 (94).…”
Section: Clinical Impact Of Nanoparticle-induced Complement Activationmentioning
confidence: 99%
“…Of note, Kurtovic et al . 45,46 found that complement fixing capability of sera from immunized infant and child recipients of the RTS,S vaccine declined rapidly after immunization and this decline paralleled the decline both in IgG complement fixing isotypes and protection against severe disease. While this finding suggests further justification for the use of the AddaVax adjuvant in subsequent vaccine trials, Potocnjak et al .…”
Section: Discussionmentioning
confidence: 98%